ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KOMUNIKASI PETANI KELAPA DI KABUPATEN INDRAGIRI HILIR - Nofitri Handayani; Roza Yulida; Yulia Andriani (JSEP (Journal of Social and Agricultural Economics), 2021)
The role of two-way development communication (convergence) is important so that coconut farmers can obtain information and determine the right farming technology towards farming management which is increasingly advanced in increasing the capacity of coconut farmers. Convergence to increase the capacity of farmers can be achieved well if there is an understanding between farmers in the process. For this reason, it is necessary to have good communication in farming activities between fellow farming actors. This study aims to: (1) To describe the communication elements of coconut farmers in Indragiri Hilir Regency, (2) to describe the communication behavior of coconut farmers in Indragiri Hilir Regency, (3) to analyze the factors which influence the communication behavior of coconut farmers in Indragiri Hilir Regency. . The method used in this research is a survey method. The population of this study consists of people who work as independent farmers, being members of farmer group, and having participated in extension activities and being included as inhabitants in Keritang and Reteh Districts, Indragiri Hilir Regency. The sampling in this study is carried out by purposive sampling with a total sample of 140 farmers. The results of the study illustrate that all variables influence coconut communication behavior in Indragiri Hilir Regency. But the differences are the direction of the relationship and the level of significance. The factor that positively and significantly influences farmer behavior in Indragiri Hilir Regency is the variable of communication media.